2008
DOI: 10.1016/j.nano.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-conjugated TiO2-DNA oligonucleotide nanoconjugates show prolonged intracellular retention period and T1-weighted contrast enhancement in magnetic resonance images

Abstract: Nanoconjugates composed of TiO 2 nanoparticles, DNA oligonucleotides and a gadolinium contrast agent were synthesized for use in magnetic resonance imaging. Transfection of cultured cancer cells with these nanoconjugates showed them to be superior to the free contrast agent of same formulation with regard to 1) intracellular accumulation, 2) retention and 3) subcellular localization. Our results have shown that 48 hours after treatment, the concentration of gadolinium in nanoconjugate treated cells was 1000 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…The scale in b also applies to a. (20,21). To our knowledge, our study represents the first functional characterization of murine DCIS with DCE MR imaging, which has an advantage over characterization of DCIS in humans: Ducts with DCIS can be clearly depicted without contrast material injection; therefore, an ROI can be placed directly on the neoplastic duct to enable one to more accurately measure its kinetic parameters, thereby minimizing the partial voluming that complicates human kinetic data.…”
Section: Discussionmentioning
confidence: 99%
“…The scale in b also applies to a. (20,21). To our knowledge, our study represents the first functional characterization of murine DCIS with DCE MR imaging, which has an advantage over characterization of DCIS in humans: Ducts with DCIS can be clearly depicted without contrast material injection; therefore, an ROI can be placed directly on the neoplastic duct to enable one to more accurately measure its kinetic parameters, thereby minimizing the partial voluming that complicates human kinetic data.…”
Section: Discussionmentioning
confidence: 99%
“…In effect, these results clearly show that, YO NCs possesses both fluorescence and magnetic functionalities suitable for bi-modal imaging. Nanocrystals based MR imaging has significant advantages over currently used Gd 3þ -DTPA complexes because of possible disease targeting capability and adjustable (PEGylation) in vivo circulation life time [54][55][56][57]. In addition, when each individual NCs, with high local concentration of magnetic ions, are accumulated within intra-cellular region, better contrast of tissue will be possible.…”
Section: Magnetic Resonance Imaging Using Yo Ncsmentioning
confidence: 99%
“…SR-XRF imaging confirmed that they were specifically retained in the mitochondria or nucleoli, thus creating a locally increased concentration of the oligonucleotide. In other studies, nanoconjugates composed of TiO 2 nanoparticles with DNA oligonucleotides and a gadolinium contrast agent were synthesized for use in magnetic resonance imaging (Endres et al 2008;Paunesku et al 2008). Transfection of cultured cancer cells with these nanoconjugates showed them to be superior to the free contrast agent of the same formulation with regard to intracellular accumulation, retention and subcellular localization.…”
Section: Examples Of Applicationmentioning
confidence: 99%